Design of a remote 3D printing laboratory prototype to be implemented at the Universidad Cooperativa de Colombia - et. al., Brayan Bernal, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This paper presents the design of a remote access laboratory, which will allow students and professors to interact and perform through the Internet, modeling processes and CAD printing practices by means of a 3D printer. It is proposed to implement a hardware and software system that will allow to monitor and control variables remotely, from a computer, located in the automation laboratory of the Universidad Cooperativa de Colombia, Bogotá campus. The main problem that motivated the development of this research, arises from the current pandemic and the impact it generated for the Universidad Cooperativa de Colombia, forcing it to temporarily close its headquarters and reinvent its teaching models, although there are different technological platforms that successfully replace the classroom teaching model through virtuality, the institution still has a major drawback with the development of their practical classes. This research was carried out through the analysis of data that allowed to accurately identify the type of practices, the number of students per practice and the most used laboratory equipment, which was done in order to identify the different variables that led to determine the type of laboratory practice that would fit the design of the remote laboratory.